2023
DOI: 10.1111/wre.12581
|View full text |Cite
|
Sign up to set email alerts
|

Weed control in a pesticide‐free farming system with mineral fertilisers

Abstract: Negative impacts of pesticides on the environment and human health, the risk of pesticide residues in the food chain, and the problems with herbicide-resistant weed biotypes support the need for alternative cropping systems. The objective of this study was to investigate weed populations, weed management and crop yield in a pesticide-free cropping system with the use of mineral fertilisers. Conventional-, organic-and mineral-ecological cropping systems (MECS) with 6-year crop rotations including winter wheat, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Traditional irrigation systems of flood irrigation and hand watering with the utilization of available sources of water, rainwater harvest, wastewater, and sewage as fertilizer [86][87][88][89] Applications of in-organic agriculture use drip irrigation and overhead irrigation with water conservation strategies through mulching [90] Conventional agricultural systems use large quantities of irrigation fresh water and fertilizers [91] Weed control Weed management strategies Nonchemical weed strategies used in traditional farming, such as crop rotations, cover crops, intercropping, and hand weeding [92] Increasing seeding rate suppresses the development of weeds through the use of mulch and long-term weed seedbank management [93,94] Intensive mechanical weeding and chemical weed control [95] Table 4. Cont.…”
Section: Irrigationmentioning
confidence: 99%
“…Traditional irrigation systems of flood irrigation and hand watering with the utilization of available sources of water, rainwater harvest, wastewater, and sewage as fertilizer [86][87][88][89] Applications of in-organic agriculture use drip irrigation and overhead irrigation with water conservation strategies through mulching [90] Conventional agricultural systems use large quantities of irrigation fresh water and fertilizers [91] Weed control Weed management strategies Nonchemical weed strategies used in traditional farming, such as crop rotations, cover crops, intercropping, and hand weeding [92] Increasing seeding rate suppresses the development of weeds through the use of mulch and long-term weed seedbank management [93,94] Intensive mechanical weeding and chemical weed control [95] Table 4. Cont.…”
Section: Irrigationmentioning
confidence: 99%
“…However, the productivity, labor efficiency, and yield stability of organic farming are considerably lower than those of conventional farming systems. It was confirmed that when crops were grown using mineral fertilizers to improve this, productivity was increased compared with organic farming, and environmental risks associated with pesticide use were prevented [9]. Additionally, mineral fertilizers can affect soil microbial communities and consequently soil quality, which in turn affects plant growth, so it is important to better understand the effects of mineral fertilizers [10].…”
Section: Introductionmentioning
confidence: 97%